Contribution à l’étude des nanostructures magnétiques types nanofils et nanotubes à structures hexagonales : Méthode de Monte-Carlo - NMAILA Badreddine (Faculté des Sciences de Rabat, 2022)
Magnetic nanowires and nanotubes have been widely studied for their various applications, ranging from information storage to biomedical. This multitude of functionalities of such magnetic nanostructures are due to their nanometric sizes, which generate atypical phenomena. In this logic, several theoretical and experimental works have been devoted to the exploration of the magnetic properties of this type of nanomaterials. The aim of this thesis is to study the magnetic and thermodynamic properties of mixed-spin nanowires and nanotubes with hexagonal structure, using Monte-Carlo numerical simulation based on the Metropolis algorithm. In order to achieve our objectives, we put a practical plan composed of two parts: one theoretical and conceptual and the second has a practical aspect. In the first part, we presented in brief generalities on magnetism,
Contribution to the study of magnetic nanostructures like nanowires and nanotubes with hexagonal structures: Monte-Carlo method
Keywords: Nanofils; nanotube; propriétés magnétiques; spin mixte; couche alterné; cœur; coquille; simulation Monte Carlo.; Physique